Kegiatan Penyiangan Bahan Pustaka (Weeding) di Perpustakaan Universitas Negeri Padang - Rahayu, Astuni; Rahmah, Elva (Ilmu Informasi Perpustakaan dan Kearsipan, 2013)
This paper focuses on the management of library materials weeding activityÂ  at library of Padang State University. The purpose of this paper are (1) to describe the procedure in weeding activities attheLibrary of Padang State University and (2) to describe any obstacles encountered in the process of weeding at the Library of the State University of Padang. The type of this research isqualitative research through observation and interview.The resultsof the research aresummarized as follow.First, the process of weeding activity management atthe Library of Padang State University has not been effective yet, this activity is still limited to the separation of collection / library materials. Second, obstacles faced in weeding activity management atthe Library of Padang State University is the absence of a written policy in weeding activities management and the absence of follow-up after doing weeding activity. Keywords: library material weeding; weeding; material library